2023
DOI: 10.1002/smll.202307685
|View full text |Cite
|
Sign up to set email alerts
|

Structural Engineering of Co‐Metal–Organic Frameworks via Ce Incorporation for Improved Oxygen Evolution

Yuanyuan Liao,
Yue Xiao,
Zhiquan Li
et al.

Abstract: The rational design of metal–organic framework (MOF)‐based electrocatalysts plays a key role in achieving high‐efficiency oxygen evolution reaction (OER). Herein, a synergetic morphology and electronic structure engineering strategy are proposed to design a Co‐MOF nanoflower grown on carbon paper via rare‐earth cerium doping (CoCe‐MOF/CP). Compared with Co‐MOF/CP, the developed CoCe‐MOF/CP exhibited superior OER performance with a low overpotential of 267 mV at 10 mA cm−2 and outstanding long‐term stability ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The Co content in Co/Ce@NC and Co@NC is 15.691 and 12.382 wt %, respectively. It is observed that the Co content significantly improved in the Co/Ce@NC catalyst than the Co@NC catalyst, indicating that the dispersion of Ce doping likely increases the distance between Co sites, leading to a significant enhancement in the dispersion of Co individual atomic sites and reducing the direct aggregation of Co single atoms, thereby exhibiting a noticeable increase in the overall Co content. Additionally, the XPS analysis, Table S2, shows that the N content in Co@NC is lower than that in Co/Ce@NC. The increased N content is beneficial for the formation of catalytically active Co–N bonds and contributes to the improvement of the catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…The Co content in Co/Ce@NC and Co@NC is 15.691 and 12.382 wt %, respectively. It is observed that the Co content significantly improved in the Co/Ce@NC catalyst than the Co@NC catalyst, indicating that the dispersion of Ce doping likely increases the distance between Co sites, leading to a significant enhancement in the dispersion of Co individual atomic sites and reducing the direct aggregation of Co single atoms, thereby exhibiting a noticeable increase in the overall Co content. Additionally, the XPS analysis, Table S2, shows that the N content in Co@NC is lower than that in Co/Ce@NC. The increased N content is beneficial for the formation of catalytically active Co–N bonds and contributes to the improvement of the catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to their individual components, heterojunctions exhibit distinct traits that make them valuable in materials science, catalysis, and energy research. The development of nanoscience and technology has led to various synthesis methods for heterojunctions, enabling more effective fundamental studies and practical applications. Metal–organic frameworks (MOFs) possess inherent qualities such as facile accessibility of channels, active metal nodes that are evenly distributed, and a wide range of coordination environments, which render them immensely versatile frameworks for fabricating transition metal-based electrocatalysts characterized by exceptional levels of efficiency. Especially, Co-based MOFs have demonstrated great potential in OER. Coincidentally, CoFe layer double hydroxide (LDH) has been widely recognized as an exceptionally efficient catalyst for OER, which can be attributed to the synergistic effects between Co and Fe metals, which significantly enhance the inherent reactivity of each active site. The controlled and precise deposition of CoFe-LDH onto the surface of Co-based MOFs represents a promising strategy to enhance the catalytic activity for OER by synergistically harnessing the advantageous properties of both materials. However, the feasibility of fabricating CoFe-LDH/Co-MOF heterostructures with a hollow morphology and subsequently optimizing the local electronic structure to significantly augment the OER activity remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metal electrocatalysts like RuO 2 and IrO 2 were extensively employed for constructing active OER catalysts. [22][23][24] Still, these catalysts had drawbacks such as substantial expenses and inadequate stability. As a result, it is critical to investigate low-cost and highefficiency OER electrocatalysts and develop a viable catalyst design strategy.…”
Section: Introductionmentioning
confidence: 99%